Poverty Alleviation Through Zakat Impact: MSMES and The National Zakat Collection Agency (BAZNAS) Studies - Ahmad Afif; Ade Wirman Syafei; Etom Katamsi (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
This research examines Islamic philanthropic zakat schemes as funding mechanisms to strengthen poverty alleviation efforts. A zakat distribution model centred on Micro, Small, and Medium Enterprises (MSMEs) will be proposed as a key recommendation for stakeholders, particularly zakat communities and MSMES actors. This methodology employs quantitative analysis of secondary data, collected via a probability sampling approach to ensure all components or samples have an equal likelihood of inclusion. Data analysis is conducted using Partial Least Squares Structural Equation Modelling (PLS-SEM) via SmartPLS software. For the findings, All hypotheses were accepted with an average significant correlation, indicating robust mutual effects among latent variables. However, the 2024 poverty gap identified by the National Zakat Collection Agency (BAZNAS) necessitates implementing collaborative zakat-MSMEs schemes. The Key MSMEs indicators include digital ecosystems, production growth, and value-added sharing. The paper urges national zakat systems, MSMEs, and communities to align MSMEs programmes with zakat distribution frameworks to optimise poverty reduction.